Interaction in collaborative writing between international and domestic students in an Indonesian university - Dwi Rahayu (Studies in English Language and Education, 2020)
This research investigates verbal interaction in collaborative writing between students from two countries with different L1 when writing an academic essay in a foreign language writing class. Eight students from Indonesia and China participated, and were divided into Indonesian-Indonesian pairs and Indonesian-Chinese pairs. Using the method of qualitative content analysis, the transcripts from their communication were coded inductively and then categorized. The findings denote that there are three categories in their spoken interaction: what to write (ideas), where to write (structural organization), and how to write (language-related). Similarly, all pairs focused their discussions on ‘what to write’ (ideas to be written in the essays). However, Indonesian-Indonesian pairs also discussed ‘the language-related aspects’ mostly about lexical choice and the meaning, more than the mixed pairs. The Indonesian-Chinese pairs conversed, in most of their time, about the content through sharing, explaining, and negotiating their ideas. As the implication, in order to produce an essay with the same length and type, the mixed pairs executed more time in their spoken interaction.